Multi-blade shedding in turbines with different casing and blade tip architectures - Eryilmaz, Ibrahim; Guenchi, Biläl; Pachidis, Vassilios (Elsevier, 2019)
A shaft failure in a gas turbine engine results in the decoupling of the turbine and the compressor. The turbine continues extracting work from the air flow causing the acceleration of the free-running turbine which can result in debris release or even disc burst. Post shaft failure the structural integrity of the engine must be guaranteed for product safety and certification purposes. To achieve this, speed limiting systems have to be integrated. One common method is friction between the rotor and stationary structures which occurs during unlocated failures where the bearing arrangement allows axial movement of the rotor under end load. Another possible mechanism is the destruction of the turbine rotor blades such that they cease to extract power from the incoming flow, decelerating progressively. Blade shedding involves rupture of blades which may result in their containment within the casing or rupture of the turbine casing. This research investigates the effects of excessive damage as blades rupture in the high-pressure turbine of a large civil engine. The research investigates different casing inclinations and shrouded/unshrouded blade configurations respectively. The nonlinear finite element software LS-DYNA is used to model two blade release scenarios which are; i) simultaneous release of all blades, and ii) simultaneous sectoral release of blades. The blades are released from firtrees considering the worst case scenario from a containment point of view. It is observed that a sector having a sufficient number of blades can result in the same effect caused by all blades impacting the casing. Containment requirements of shrouded and unshrouded rotors with different casing inclinations are compared as a function of the blade kinetic energy. Provided that the blade mass is kept constant, the effect of the casing inclination is found to be dominant when compared to the effect of blade tip geometry. Together with a rotor overspeed trajectory, the containment requirement of a simultaneous multi-blade shedding application for disk burst prevention is given. The research provides improved understanding of blade tip-to-casing interactions, to be used as an overspeed prevention mechanism, and contributes towards developing design guidelines for the next generation of aero engines in terms of fail-safe engine architectures.
Keywords: Shaft failure; Turbine overspeed; Blade rupture; LS-DYNA; Finite element analysis